Spot mode excitation for multimode fiber - Fazea, Yousef; Amphawan, Angela; Ahmad, Amran (2015)
Data centers are referred to as the brain of the Internet.In data centers, multimode fiber is typically used to ensure scalability and reliability. Due to the continuous growth of Internet users which demands increasing data capacity, mode division multiplexing (MDM) presents itself as a potential candidate for providing an additional degree of multiplexing freedom through the propagation of distinct channels on different fiber modes.This paper investigates the effects of launching a spot mode with different vortex orders using a vertical-cavity surface-emitting laser (VCSEL) array and a vortex lens.A transmission of 12Gbit/s over distance of 1km is achieved at a wavelength of 1550.12nm